Why a critical geopolitics cannot be Confucian. Issue 2 (July 2021) - Gonzalez-Vicente, Ruben
In this commentary, I welcome An et al.'s (2021) commitment to explore the role of Confucian thought in the contemporary practices of statehood in the People's Republic of China (PRC). Nonetheless, I also take issue with the authors' argument that a Confucian geopolitics is needed to replace inadequate 'Western geopolitical frameworks'. Confucian philosophies promote a hierarchical social order based on authority and subordination, and the way in which they are selectively and strategically utilized in contemporary China represents an important subject of analysis. However, they should not be viewed as a framework of analysis, as they obscure rather than shed light on spatial and class struggles – even in the hybridized stylization endorsed by An et al. Critical political economic and critical geopolitical perspectives with a global theoretical orientation and a knowledge of place and culture offer more promise in the disentangling of state practices and social relations in the PRC.